Alleviation of Hepatic Ischemia Reperfusion Injury by Oleanolic Acid Pretreating via Reducing HMGB1 Release and Inhibiting Apoptosis and Autophagy - Wenwen Wang; Liwei Wu; Jingjing Li; Jie Ji; Kan Chen; Qiang Yu; Sainan Li; Jiao Feng; Tong Liu; Jie Zhang; Jiaojiao Chen; Yuting Zhou; et al. (Mediators of Inflammation)
Hepatic ischemia reperfusion (IR) injury (IRI) occurs during liver transplantation, hepatectomy, and hemorrhagic shock. Oleanolic acid (OA) is a natural compound with antioxidant and anti-inflammatory activity that has been used to treat liver disorders in clinical practice for several years. Here, we investigated the effects and underlying mechanisms of OA in hepatic IRI. A 60-minute partial (70%) hepatic, warm, ischemic reperfusion model was established in BALB/c mice, and two doses (30 and 60 mg/kg) of OA were administered intragastrically for 7 consecutive days prior to hepatic IR. Orbital blood and liver specimens were collected at 2, 8, and 24 h after IR. The results showed that OA preconditioning significantly alleviated hepatic injury, as evidenced by decreased alanine aminotransferase and aspartate aminotransferase levels; improved histology, inhibition of JNK phosphorylation, and high mobility group box 1 (HMGB1); and tumor necrosis factor-α downregulation in hepatic IR mice. OA upregulated Bcl-2 and downregulated caspase-3, caspase-9, Bax, Beclin 1, and LC3, which play crucial roles in the regulation of apoptosis and autophagy. These findings highlighted the protective effects of OA against hepatic IRI mediated by the inhibition of apoptosis and autophagy and the release of HMGB1, which acted as a late inflammatory mediator in hepatic IRI.